2020
DOI: 10.3390/polym12112451
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties and pH Sensitive Swelling of Insitu Formed Silver-Curcumin Nanocomposite Based Chitosan Hydrogel

Abstract: A simple method was used to prepare curcumin/silver nanocomposite based chitosan hydrogel. In an alkaline medium, chitosan and chitosan nanocomposite hydrogels were prepared using the physical crosslinking method. The prepared hydrogels were stable for a long period at room temperature. In one step, silver nanoparticles were prepared insitu using silver nitrate solution and curcumin oxide within the hydrogel network formation. In the meantime, curcumin compound served as both a reducing and stabilizing agent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 38 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…15 This behavior provides the possibility to use for applications such as drug delivery by adapting to different pH environments. 15,17 Synthesis of HTCC−Ag NP Hydrogels. The concentration of silver nitrate used in this process followed a careful optimization which relied on a visualization of the system using HR-SEM and was determined to be 0.1 M (Figure S3.1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…15 This behavior provides the possibility to use for applications such as drug delivery by adapting to different pH environments. 15,17 Synthesis of HTCC−Ag NP Hydrogels. The concentration of silver nitrate used in this process followed a careful optimization which relied on a visualization of the system using HR-SEM and was determined to be 0.1 M (Figure S3.1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other bands are observed in the region between 1000 cm −1 and 1300 cm −1 . All bands could be ascribed to the configuration of the symmetric and asymmetric C-O-C groups [39].…”
Section: Ftir Analysismentioning
confidence: 95%
“…They found that the swelling degrees of curcumin-silver/chitosan hydrogel were higher than chitosan hydrogel at pH 4 and 7. This may be due to the presence of curcumin-silver nanoparticles in the hydrogel, which expands the formed hydrogel network [9]. But higher amounts of NGs and lower amount of hydrogel (15:85 and 20:80) reduced the swelling degree.…”
Section: Swelling Degreementioning
confidence: 99%
“…The presence of CSG hydrogel increases the number of hydrophilic groups, which results in more hydration and swelling [51]. The presence of NG: HYD ratio of 10:90, expands the composite network and increases the porous matrix, and consequently the composite absorbs more water [9]. Elhadi et al investigated the swelling properties of chitosan hydrogel based on curcumin-silver nanocomposite.…”
Section: Swelling Degreementioning
confidence: 99%